Assistance in Non-Profit Financial Statements at The Al-Qur'an Education Institution Through The Implementation of Isak 35 - Firdahus, M. Surgo (TAAWUN, 2025)
This service aims to analyze the assets of Al-Qur’an Education institutions in financial statements and to analyze achievements in non-profit financial statements based on Isak 35 on Al-Qur’an Education Institutions in Bojonegoro. The method used in this community service is Asset-Based Community Development (ABCD), with various stages, namely inculturation, discovery, design, definition, and reflection. The results of community service in the form of managing economic resources in the financial reports of Al-Qur'an Education (TPQ) play a crucial role in ensuring operational sustainability and improving the quality of educational services. By implementing ISAK 35 standards, TPQ can increase transparency, accountability, and efficiency in the use of funds, which in turn will strengthen the credibility of the institution and increase public and donor trust. The strategy of strengthening the performance of ISAK 35-based financial reports through the ABCD method also helps create synergy between management, society, and stakeholders to support the sustainability of TPQ. Strengthening these financial reports not only provides a solid foundation for TPQ in achieving educational goals but also increases transparency and accountability. This encourages public confidence to more actively support TPQ programs, both through direct participation and resource contributions, thereby strengthening the operational sustainability of the institution and providing a real positive impact on educational development and empowerment of the surrounding community.